Immediate Effects of Selective Logging on Understorey Birds in Ulu Muda Forest Reserve, Kedah, Malaysia - Rosli, Zamri (2001)
This study was carried out to determine understorey bird species composition before and immediately (less then one year) after logging. The main objectives were to determine: (i) the trophic structure related to the feeding guild, (ii) the diversity in terms of species diversity, species richness and species evenness) and (ii) to generate a species list for understorey bird population before and immediately after logging. The study was conducted in compartment 28/29, Ulu Muda Forest Reserve, Kedah, Malaysia. This area is a hill forest covering an area of 791.2 ha. It was harvested using selective logging method in 1997 and harvesting was completed at the end of 1999. Mist-netting method was used to obtain the information on understorey bird species. A total of 75 species with 175 individuals were recorded before logging and 61 species with 385 individuals were recorded immediately after logging. The Babblers group decreased immediately after logging. However, the bulbuls and spiderhunters increased immediately after logging. The Insectivore group was found to dominate the forest before logging followed by insectivore/frugivore and frugivore groups. However, the insectivore/frugivore group dominated the area immediately after logging, followed by insectivore and nectarivore/insectivorel frugivore groups. The analysis of feeding guild also showed that the arboreal foliage gleaning insectivore guild dominated the primary forest in terms of species composition and number of individuals, but their numbers decreased immediately after logging. The arboreal foliage gleaning insectivore/frugivore was found to be higher in terms of the number of species and individuals immediately after logging. The values of species diversity index (H'), species richness index (R) and species evenness index (E) were also significantly higher before logging compared with the values immediately after logging. The changes in forest vegetation and microclimate were the main factors which affected the composition and diversity of understorey bird species. Thus, logging has changed the composition, the trophic and feeding guild structures as well as the diversity of understorey bird species.